2018
DOI: 10.1126/sciadv.aao6596
|View full text |Cite
|
Sign up to set email alerts
|

Areas prone to slow slip events impede earthquake rupture propagation and promote afterslip

Abstract: Frequent slow slip events and rapid postseismic slip reveal persistent aseismic fault areas delineating future seismic ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
180
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(204 citation statements)
references
References 41 publications
24
180
0
Order By: Relevance
“…The postseismic observations of larger earthquakes were made by a range of researchers over a range of timescales, from days to years after the earthquakes, as listed in Table S3. The large‐event moment ratios come from 35 earthquakes numbered in Figure , from the 1: 2005 Chaman (Furuya & Satyabala, ), 2: 2008 Mogul, NV swarm (Bell et al, ), 3: 1998 San Juan Bautista (Taira et al, ), 4: 2007 Alum Rock, CA (Murray‐Moraleda & Simpson, ), 5: 2007 Ghazaband (Fattahi et al, ), 6: 2004 Parkfield (Freed, ; Langbein et al, ), 7: 2014 South Napa (Amoruso & Crescentini, ; Cheloni et al, ; Floyd et al, ), 8: 2009 L'Aquila (D'Agostino et al, ), 9: 2008 Nima‐Gaize, Tibet (Ryder et al, ), 10: 2000 Iceland (Jónsson, ), 11: 2003 San Simeon (Johanson & Bürgmann, ), 12: 2003 Zemmouri (Cetin et al, ; Mahsas et al, ), 13: 1989 Loma Prieta (Segall et al, ), 14: 1991 Racha, Georgia (Podgorski et al, ), 15: 1999 Hector Mine (Jacobs et al, ), 16: 2003 Altai (Barbot et al, ), 17: 2010 El Mayor‐Cucapah (Gonzalez‐Ortega et al, ), 18: 2011 Van (Dogan et al, ), 19: 1992 Landers (Savage & Svarc, ), 20: 1997 Manyi, Tibet (Ryder et al, ), 21: 2012 Nicoya (Hobbs et al, ; Malservisi et al, ), 22: 1994 Sanriku (Heki et al, ; Melbourne et al, ), 23: 2015 Gorkha (Sreejith et al, ), 24: 2001 Kokoxili, Tibet (Wen et al, ), 25: 1997 Kronotsky (Bürgmann et al, ), 26: 2016 Pedernales (Rolandone et al, ), 27: 2008 Wenchuan (Diao et al, ), 28: 1995 Jalisco (Melbourne et al, ), 29: 2003 Tokachi‐Oki (Miura et al, ), 30: 1995 Antofagasta (Melbourne et al, ; Pritchard & Simons, ), 31: 2015 Illapel (Shrivastava et al, ), 32: 2001 Peru (Melbourne et al, ), 33: 2005 Nias (Hsu et al, ), 34: 2010 Maule (Lin et al, ), and 35: 2004 Sumatra (Chlieh et al, ; Subarya et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postseismic observations of larger earthquakes were made by a range of researchers over a range of timescales, from days to years after the earthquakes, as listed in Table S3. The large‐event moment ratios come from 35 earthquakes numbered in Figure , from the 1: 2005 Chaman (Furuya & Satyabala, ), 2: 2008 Mogul, NV swarm (Bell et al, ), 3: 1998 San Juan Bautista (Taira et al, ), 4: 2007 Alum Rock, CA (Murray‐Moraleda & Simpson, ), 5: 2007 Ghazaband (Fattahi et al, ), 6: 2004 Parkfield (Freed, ; Langbein et al, ), 7: 2014 South Napa (Amoruso & Crescentini, ; Cheloni et al, ; Floyd et al, ), 8: 2009 L'Aquila (D'Agostino et al, ), 9: 2008 Nima‐Gaize, Tibet (Ryder et al, ), 10: 2000 Iceland (Jónsson, ), 11: 2003 San Simeon (Johanson & Bürgmann, ), 12: 2003 Zemmouri (Cetin et al, ; Mahsas et al, ), 13: 1989 Loma Prieta (Segall et al, ), 14: 1991 Racha, Georgia (Podgorski et al, ), 15: 1999 Hector Mine (Jacobs et al, ), 16: 2003 Altai (Barbot et al, ), 17: 2010 El Mayor‐Cucapah (Gonzalez‐Ortega et al, ), 18: 2011 Van (Dogan et al, ), 19: 1992 Landers (Savage & Svarc, ), 20: 1997 Manyi, Tibet (Ryder et al, ), 21: 2012 Nicoya (Hobbs et al, ; Malservisi et al, ), 22: 1994 Sanriku (Heki et al, ; Melbourne et al, ), 23: 2015 Gorkha (Sreejith et al, ), 24: 2001 Kokoxili, Tibet (Wen et al, ), 25: 1997 Kronotsky (Bürgmann et al, ), 26: 2016 Pedernales (Rolandone et al, ), 27: 2008 Wenchuan (Diao et al, ), 28: 1995 Jalisco (Melbourne et al, ), 29: 2003 Tokachi‐Oki (Miura et al, ), 30: 1995 Antofagasta (Melbourne et al, ; Pritchard & Simons, ), 31: 2015 Illapel (Shrivastava et al, ), 32: 2001 Peru (Melbourne et al, ), 33: 2005 Nias (Hsu et al, ), 34: 2010 Maule (Lin et al, ), and 35: 2004 Sumatra (Chlieh et al, ; Subarya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the varying postseismic moments could reflect fault properties. Smaller earthquakes may be more likely to occur on creeping sections of faults, perhaps on asperities surrounded by velocity‐strengthening fault sections that are more prone to large postseismic slip (e.g., Rolandone et al, ; Vaca et al, ). The postseismic moment estimates for M < 3.5 earthquakes all come from a single 20‐km‐wide fault segment near San Juan Bautista, CA, which could have particular properties (Hawthorne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we do not find any SSEs shallower than the five detected SSEs. Dixon et al () and Rolandone et al () suggested that shallower SSEs may reduce the tsunami potential along the shallow part of the plate interface because those SSEs release at least part of the accumulated slip deficit and may limit coseismic rupture propagation. These previous studies, together with the absence of shallow slow slip found in this study, may be consistent with the possibility of shallow historical tsunami earthquake (Nakamura, ) and may imply future tsunami earthquakes in the southern Ryukyu subduction zone.…”
Section: Discussionmentioning
confidence: 99%
“…SSEs have now been observed in a variety of tectonic settings, spanning timescales from seconds to years (Peng & Gomberg, 2010) and with equivalent geodetic moment magnitude from M ∼ 1 up to M ∼ 7.5 (e.g., Beroza & Ide, 2011;Ide et al, 2007). SSEs are sometimes accompanied by an increase in seismicity (Rolandone et al, 2018;Segall et al, 2006;Vallée et al, 2013) or by nonvolcanic tremors (e.g., Peng & Gomberg, 2010;Rogers & Dragert, 2003), and together represent an important mechanism of strain release in active regions. Aseismic slip also occurs as stress-driven afterslip in response to the stress change imparted by a coseismic stress drop (e.g., Marone et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Stress perturbations from a mainshock rupture can trigger spontaneous or delayed SSEs (over hours to months; e.g., Hayes et al, 2014;Hirose et al, 2012;Rolandone et al, 2018), which release stress that had built up during the previous inter-SSE interval (Bürgmann, 2018), and can also trigger transient creep (Lienkaemper et al, 1997;Wei et al, 2015) or modulate surface creep rate (Xu et al, 2018). In general, dynamic triggering of SSEs remains a rare phenomenon, and only a few cases are documented (Araki et al, 2017;Itaba & Ando, 2011;Wallace et al, 2017;Zigone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%